1993
DOI: 10.1192/pb.17.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Who makes it in psychiatry: CV predictors of success in training grades

Abstract: A recent paper by Lewis (1991) found authorship of a publication to be the only variable that significantly predicted whether applicants for a senior registrar (SR) rotation in psychiatry at a London teaching hospital were shortlisted. We have re-examined curriculum vitae (CV) predictors of shortlisting at SR level within a comparable London teaching hospital rotation (University College and Middlesex Medical School, UCMSM), and extended the study to examine applicants for the corresponding SHO/registrar (REG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Lewis (1991) found that authorship of a publication was the only variable that significantly predicted whether applicants for a senior registrar (SR) rotation in psychiatry at a London teaching hospital were shortlisted. Katona & Robertson (1993) confirmed this, and found that a publication containing original data was an even stronger predictor of success.…”
Section: Commentsupporting
confidence: 72%
“…Lewis (1991) found that authorship of a publication was the only variable that significantly predicted whether applicants for a senior registrar (SR) rotation in psychiatry at a London teaching hospital were shortlisted. Katona & Robertson (1993) confirmed this, and found that a publication containing original data was an even stronger predictor of success.…”
Section: Commentsupporting
confidence: 72%
“…Lewis (1991) found that can didates for senior registrar (SR) posts were more likely to be shortlisted if they had a 'publication'. Katona & Robertson (1993) replicated this and found that publication, particularly of 'datacontaining' articles, predicted appointments to SR posts and short-listing for registrar (reg) posts. Research experience without publication, however, did not increase the likelihood of either short-listing or appointment.…”
mentioning
confidence: 74%
“…In the last few years, the Bulletin has published articles which offer advice and support to prospective SR candidates (Tufnell, 1984;Margerison, 1987), and more recently Ratona & Robertson (1993) sur veyed the CV predictors of success for applicants to training grades in a London teaching hospital. The 'vexed question' of how much research should be expected of registrars has been discussed at the …”
Section: Referencesmentioning
confidence: 99%